Penyuluhan Peningkatan Kualitas Kemasan Produk Pada Pengrajin Tahu dan Tempe di Keluruhan Semanan, Jakarta Barat - Indriyarti, Eko Retno; Faisal, Aekram; Sabur, Moch.; Ganawati, Ganawati (Universitas Nusantara PGRI Kediri, 2021)
The situation of the Covid-19 pandemic that has not ended gives a signal that the business will continue to face uncertainties that affect the sustainability of Micro, Small and Medium Enterprises (MSMEs) in Indonesia. The purpose of community service activities for tofu and tempe craftsmen partners in Semanan village, West Jakarta is to help increase the selling value of tofu and tempe products. The method used in the implementation of this community service is to provide direct counseling at partner locations by giving explanations on how to improve the quality of the packaging of the tofu and tempe products produced. The results of this community service activity suggest three aspects of the solution, namely paying attention to the quality of the packaging related to the cleanliness of the tofu and tempe sold, maintaining the resilience of the tofu and tempe that are sold in good packaging, adding product identity to the packaging to increase the product's selling value. Response from partners is happy with this activity.